Wybrane sposoby czytania Tryptyku rzymskiego Jana Pawła II na zajęciach literackich w szkole ponadpodstawowej (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The article reflects on John Paul II’s Roman Triptych. The poem was included in the list of reading proposed for high school students. The text shows various ways of analyzing the poems contained in it, including: interpretation of the title and subtitle, determining the features of poetry, researching the structure of the poem, searching for keywords and building semantic fields around them, recalling literary, philosophical, historical and theological. By reading and considering the pieces of the Roman Triptych, teenagers have a chance to get to know better and maybe even rediscover the Holy Father as an artist of the word, priest, educator and guide in the world of values. In the poems, John Paul II describes his vision of God and man, nature and art. He contemplates and explains the Bible, bears witness to the truths arising from recognizing the nature of the relationship between man and God, based on a special bond, trust and love.